2021
DOI: 10.1371/journal.pone.0255161
|View full text |Cite|
|
Sign up to set email alerts
|

An evaluation of the chemical content and microbiological contamination of Anatolian bee venom

Abstract: Bee venom is a natural substance produced by worker bees. The aim of this research paper is to determine the characteristics of Anatolian bee venom by evaluating its chemical content and microbiological properties. Physical, chemical and microbiological analyses were performed on 25 bee venom samples from different areas of Anatolia, Turkey. Data obtained by 3-replicate studies were evaluated with normality and one-way and two-way ANOVA / Tukey tests. Chemical analyses of the bee venoms revealed average melitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Much attention has been paid to the study of the antimicrobial action of bee venom [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. These properties are due to the presence of peptide compounds, phospholipase А2, MCD (mast cell degranulating) peptide, and melittin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Much attention has been paid to the study of the antimicrobial action of bee venom [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. These properties are due to the presence of peptide compounds, phospholipase А2, MCD (mast cell degranulating) peptide, and melittin.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the well-documented diverse biological activity of this most expensive bee product. In particular, evidence has been obtained of its antimicrobial action against both bacteria (including antibiotic-resistant strains) and pathogenic fungi [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. The therapeutic effect of the external use of apitoxin in the treatment of wounds [ 24 , 25 ] as well as skin diseases [ 26 ] is largely associated with antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Purified bee venom is composed of enzymes and several active peptides, including apamin, melittin, mast cell-degranulating peptides, and adolapin, and is a natural toxin produced by Apis mellifera L. (honeybees) [43,44]. Bee venom is reported to treat back pain, rheumatoid arthritis (inflammatory disease), and skin diseases and acts as an anticancer agent in the treatment of breast cancer cells, prostate cancer cells, and lung cancer cells [45,46]. A recent study reported that bee venom was effective in periodontitis treatment, showing anti-periodontitis and anti-inflammatory effects [47].…”
Section: Introductionmentioning
confidence: 99%